Redating Schoenberg’s Announcement of the Twelve-Tone Method: A Study of Recollections - Fusako Hamao (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Arnold Schoenberg recalled that he gathered about twenty of his students in 1923, in order to announce his new compositional method based on twelve tones, which he had kept confidential for nearly two years. His reminiscences about this announcement appear several times in his writings, yet his reference to the date of the occasion varies from recollection to recollection. The reminiscences of his students are not consistent in this regard either, although “February 1923,” identified by Josef Polnauer, has been widely accepted as the date of the meeting. However, this date has become a point of debate in recent studies, along with the publications of newly uncovered documents related to Schoenberg’s announcement. In particular, a letter by Anton Webern, dated 7 January 1922, reveals that Schoenberg conducted a lecture series on his new method before 1923. In this essay, the author investigates recollections of the announcement meeting made by Schoenberg and his students to see if they contain any confusions or misunderstandings that might have caused an incorrect dating. After sorting out the details, the author discusses the unreliability of Polnauer’s dating, speculates on how the “myth” of a February 1923 meeting was created, and concludes that the first day of the lecture series (described by Webern) was actually the oft-cited announcement meeting, which most likely occurred between 23 December 1921 and 3 January 1922. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part III).